Investigating the Adsorption Behavior of Zwitterionic Surfactants on Middle Bakken Minerals - Tomiwa Isaac Oguntade; Adesina Samson Fadairo; Temitope Fred Ogunkunle; David Adebowale Oladepo; Luc Yvan Nkok (Applied Sciences)
Zwitterionic surfactants are a promising option for application in harsh reservoir conditions due to their exceptional stability, compatibility, and interfacial activity. However, surfactant adsorption remains a significant concern. This study investigates the adsorption behavior of zwitterionic surfactants was studied on complex Middle Bakken minerals under high-salinity (total dissolved solids (TDS) = 29 wt%) and high-temperature (90 °C) conditions using the spectrophotometric method. The adsorbents were prepared by grinding Bakken core plugs using a ball mill and sifting them through 40 μm mesh sieves to ensure uniform particle size distribution. The results showed that the Langmuir adsorption model accurately describes the adsorption isotherms of zwitterionic surfactants. The impact of salinity on the zwitterionic surfactants adsorption varied depending on the presence of acidic and/or basic groups in the surfactants. Using Bakken formation brine instead of brine solutions with 2% TDS resulted in a decrease in adsorption of approximately 1.06 ± 0.02 mg/g for CG3 and 0.3 ± 0.04 mg/g for both CD2 and ME1. This reduction was observed in betaine-type zwitterionic surfactants with −COO− functional groups that may gain protons, compared to their adsorption capacities in the 2% TDS brine (2.35 mg/g, 2.1 mg/g, and 1.89 mg/g, respectively). This study provides critical insights into the behavior of interfacial tension (IFT) between crude oil and surfactant solutions, which is vital for optimizing enhanced oil recovery (EOR) processes. The findings underline the importance of surfactant concentration and adsorption characteristics, offering valuable guidelines for practical applications in petroleum reservoir management. Overall, zwitterionic surfactants exhibit higher adsorption on Bakken minerals regardless of the salinity condition.